Structure optimisation and biological evaluation of bone scaffolds prepared by co-sintering of silicate and phosphate glasses. (24th October 2015) - Novajra, G.; Perdika, P.; Pisano, R.; Miola, M.; Bari, A.; Jones, J. R.; Detsch, R.; Boccaccini, A. R.; Vitale-Brovarone, C.
Abstract : A degradable phosphate glass (ICEL) and a bioactive silicate glass (CEL2) were mixed in different ratios (wt-%: 100%ICEL, 70%ICEL–30%CEL2, 30%ICEL–70%CEL2, 100%CEL2; codes 100-0, 70-30, 30-70, 0-100) and then co-sintered to obtain three-dimensional porous scaffolds by gel casting foaming. Thermal analyses were carried out on the glass mixtures and were used as a starting point for the optimisation of the scaffold sintering treatment. The microcomputed tomography and field emission scanning electron microscope analyses allowed the selection of the optimal sintering temperature to obtain an adequate structure in terms of total and open porosity. The scaffolds showed an increasing solubility with increasing ICEL glass content, and for 30-70 and 0-100, the precipitation of hydroxyapatite in simulated body fluid was observed. In vitro tests indicated that all the scaffolds showed no cytotoxic effect. The co-sintering of silicate and phosphate glasses showed to be a promising strategy to tailor the scaffold osteoconductivity, degradation and bioactivity.